Effects of Buriganga and Turag River Water on the Yield and Heavy Metal Contents of Indian Spinach - Nawshin, N; Sadab, FR; Chowdhury, MAH; Baten, MA (Journal of Environmental Science and Natural Resources, 2017)
There are different types of essential nutrients are found in vegetables which are good for human health. But now a days the vegetables which are irrigated with Buriganga and Turag river water may be contaminated with heavy metals because of industrial effluents discharge into the Buriganga and Turag river water. The present study was conducted to investigate the levels of heavy metals like Lead (Pb), Cadmium (Cd), Cupper (Cu), Chromium (Cr), Zinc (Zn), Arsenic (As), Nickel (Ni), and Iron (Fe) in Indian Spinach irrigated with polluted Buriganga and Turag river water. Heavy metals contaminated water and vegetable samples were analyzed by Atomic Absorption Spectrophotometer. The Pb, Cd, Ni, Cr, As, Zn, and Cu contents in Buriganga river water applied in Indian spinach ranged from 0.798-2.06, 0.011-0.60, 0.001-3.87, 0.378-1.25, 0.001-0.610, 6.21-23.24, and 2.01-13.69 ?g g-1, respectively and those of Turag river water ranged from 0.023- 0.781, 0.001-0.610, 0.001-0.360, 0.133-0.279, 0.001-0.360, 3.16-8.97, and 0.210-6.47 ?g g-1, respectively. The root and shoot length was decreased from 5.3 to 3.2 cm and from 7.2 to 5.5 cm for Buriganga river water applied plant samples. The root and shoot length of Turag river water applied plant samples were decreased from 3.83 to 3.10 cm and 6.93 to 6.18 cm, respectively. The number of leaves was decreased from 7.46 to 5.58 and 8.69 to 5.32 for Buriganga and Turag river water applied plant samples, respectively. The yield of Buriganga and Turag river water applied Indian spinach sample decreased 23.06% and 24.70% from the control plant sample. It is recommended that in spinach plant the concentration of Pd, Zn and Cu crossed the standard limits of FAO and WHO, indicating a potential risk to human body. Awareness should be created among the farmers about the serious consequences of using polluted river water for growing leafy vegetables in city areas. J. Environ. Sci. & Natural Resources, 9(2): 15-20 2016